MEMBINA MOTIVASI BELAJAR BAHASA INGGRIS DENGAN MENERAPKAN MATA KULIAH ENGLISH FOR YOUNG LEARNERS PADA ANAK TK DI DAERAH PERBATASAN - Wisrance, Maria Wihelmina (Universitas Sanata Dharma, 2025)
Since teaching English is a crucial policy in Indonesian education and a global demand, this community service program aimed to help learners at the primary level by encouraging their eagerness to learn English as early as possible. This service program was conducted at Petra Kindergarten, located in Kefamenanu, Timor Tengah Utara Regency. The participants in this program are children aged 4 to 6. The program aimed to motivate those children to learn English by providing an enjoyable class. Additionally, this program facilitated English Education Study Program students at Timor University to apply the theory they had learned in the EYL subject in real-world practice. This service program was done by implementing the edutainment method using games, songs, and other interesting media. The program was held for five months and divided into 20 sessions. The evaluation revealed that the children showed significant improvement in mastering English vocabulary and speaking skills, particularly their vocabulary related to classrooms, schools, body parts, food, drinks, and other objects around them, which increased by approximately 30%. This clearly demonstrates that the program has significantly increased the children’s willingness and motivation to learn English at Petra Kindergarten. The team hopes that this program can serve as a model for other institutions in improving English learning at the preschool level through edutainment methods.